Ontology of zakat management system - Harun, Hazaruddin; Nordin, Nazib; Hussain, Azham (2008)
Zakat Management System is a system that manages all the processes that are involved in zakat activities.At present, there exist no standard which can be utilized to develop Zakat Management System. In order to support the development of Zakat Management System, this paper provides the ontology of Zakat Management System aimed specifically to share the knowledge of zakat. Each person who are involved in the development of this system will hopefully share a common understanding of Zakat Management System. This in turn will make the process of development faster.